Making a Modified Batak Toba Bridal Bun Video Tutorial with Modern Pineapple Fiber Technique - Sellies Qori Andiani; Titin Supiani (Jurnal Tata Rias dan Kecantikan, 2022)
The development of beauty trends in the world, especially hair makeup, has changed and increased. Through technological developments, the world of beauty can be easily understood, one of which is through the use of modified Toba Batak bridal bun video tutorials using the pineapple fiber technique. This final project aims to produce a Modified Toba Batak Bridal Bun Tutorial Video with Modern Pineapple Fiber Technique which is suitable for reference and learning resources. Making videos uses 3 stages, namely Pre-production, Production and post-production stages. The feasibility test was carried out by 2 people, namely, material experts and media experts. On the results of the overall assessment and suitability of this Modified Toba Batak Bridal Bun Video Tutorial, it resulted in an assessment of 95% for material experts and 97% for media experts who were in the very good category in overall results. Based on these results, it is concluded that the video tutorial is very suitable to be used as a reference and learning resource for students of Jakarta State University and the general public.